Senegal : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Joint Staff Advisory Note reviews Senegal's Second Poverty Reduction Strategy Paper (PRSP-II), and provides advice on key priorities for strengthening the updated strategy and promoting its effective implementation. The PRSP-II, covering 2006-10, builds on lessons learned during the implementation of the 2003-05 Senegal Poverty Reduction Strategy (PRSP-I). The PRSP-II pushes the poverty reduction agenda forward so as to meet the objective of raising economic growth to about 7 percent per year necessary to halve poverty by 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet